The âModernâ Concept of Erga Omnes to Establish the Obligation of Impunity Eradication: Towards the Primacy Jurisdiction of the International Criminal Court - Christianti, Diajeng Wulan (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2018)
AbstractDespite the fact that there is no universally accepted definition, international crimes are related closely to civilian casualties and mass destruction, armed conflict, patriotism, and involvement of state. Consequently, domestic jurisdictions often fail to prosecute perpetrators, leaving international law enforcement as the only option for accountability. However, international law remains incarcerated within state-centric image. In the absence of their consent, states do not perceive that they have a duty to prosecute perpetrators of international crimes. This situation triggers impunity. On the other hand, there is a long-standing recognition of jus cogens as a universal and superior norm and the concept of erga omnes obligation for violation on important rights. These two concepts are based on the interest of âthe whole international communityâ. All states are required to comply the concepts despite of their willingness to be bound by these concepts. This study was conducted to identify the characters of erga omnes obligation and to examine the possibilities of their application to prosecute international crimes. It also discusses the difficulties of the current erga omnes concept to enforce obligation of impunity eradication, especially for International Criminal Court (ICC). As the one and only permanent international criminal court, ICC received accusations and criticisms for being âa selective justiceâ. Hence, this study puts forward a âmodernâ erga omnes concept as shift of paradigm from âstate sovereigntyâ to âhumanity-based approachâ. This modern concept is a significant theoretical foundation for the primacy jurisdiction of the ICC because this primacy is the only option that the ICC can apply universally to achieve global justice.AbstrakMeskipun tidak ada definisi yang disepakati secara internasional, kejahatan internasional seringkali dikaitkan dengan korban sipil, kehancuran luar biasa, konflik bersenjata dan semangat patriotisme serta keterlibatan negara. Akibatnya, hukum nasional seringkali gagal dalam menuntut pelaku sehingga mekanisme internasional menjadi satu-satunya cara untuk menuntut pertanggungjawaban pidana pelaku. Namun, hukum internasional masih terpenjara dalam sistem yang terpusat pada negara, sehingga tanpa adanya kesepakatan, negara tidak merasa harus patuh pada kewajiban untuk menuntut pelaku. Hal ini melahirkan iklim impunitas. Sementara itu, hukum internasional sejak lama telah mengakui keberadaan sebuah norma yang universal dan superior yakni jus cogens serta konsep kewajiban erga omnes sebagai sebuah konsekuensi pelanggaran dari suatu âhak-hak yang pentingâ. Kedua konsep hukum tersebut mendasarkan pada kepentingan masyarakat internasional secara keseluruhan sehingga mengharuskan semua negara untuk patuh terlepas dari keinginan mereka untuk terikat atau tidak dengan norma tersebut. Artikel ini mengidentifikasi karakter dari kewajiban erga omnes dan menelaah apakah karakter tersebut terpenuhi dalam sifat dari kewajiban untuk menghapuskan impunitas. Artikel ini kemudian memaparkan kesulitan-kesulitan yang dihadapi bagi konsep erga omnes saat ini dalam perannya menegakkan kewajiban untuk menghapuskan impunitas khususnya bagi International Criminal Court (ICC) untuk berlaku universal. Sebagai satu-satunya mahkamah pidana internasional permanen, ICC telah mendapat banyak kritikan karena dianggap masih âpilih-pilihâ dalam menerapkan keadilan. Artikel ini menawarkan konsep erga omnes âmodernâ sebagai dasar untuk merubah paradigma dari pendekatan berbasis kedaulatan negara menjadi berbasis umat manusia. Konsep modern ini dapat menjadi landasan teori bagi ICC untuk memberlakukan primacy jurisdiction kepada seluruh negara dan mewujudkan keadilan global. DOI: https://doi.org/10.22304/pjih.v5n2.a1